Deep Learning for Teachers: Toward Innovative and Sustainable Education - Marpaung, Rini Rita T. Marpaung; Berti, Berti Yolida; Median, Median Agus; Nadya, Nadya Meriza; Dian, Dian Ratna (Outline Publisher, 2025)
The training program “Deep Learning for Biology Teachers: Towards Innovative and Sustainable Learning” aims to enhance Biology teachers’ competence in developing instructional tools based on deep learning principles that support sustainable education. The deep learning approach plays a vital role in Biology education as it helps students understand concepts more deeply, connect them with real-world contexts, and build awareness of global issues such as environmental protection and sustainability. The success of this approach depends on the availability of well-designed learning instruments, including syllabi, lesson plans, worksheets, and authentic assessments aligned with deep learning and sustainability goals. The program’s implementation includes a pretest, material presentation, discussions, simulations, and a posttest. The pretest assesses participants’ initial knowledge, while interactive sessions explore the relationship between Biology learning, environmental issues, and disaster mitigation strategies. The posttest then evaluates teachers’ progress in designing innovative, sustainability-oriented instructional instruments. The results show improved understanding and competence among MGMP Biology participants, indicating that the training makes a tangible contribution to enhancing the quality of Biology education relevant to 21st-century challenges.